Water and land security in drylands : response to climate change - Ouessar, Mohamed; Gabriels, D.; Tsunekawa, Atsushi, 1960-; Evett, Steven (Springer, 2017)
This book presents recent lessons learned in the context of research and development for various dryland ecosystems, focusing on water resources management, land and vegetation cover degradation and remediation, and socioeconomic aspects, as well as integrated approaches to ensuring water and land security in view of the current and predicted climate change. As water and land are the essential bases of food production, the management of these natural resources is becoming a cornerstone for the development of dryland populations. The book gathers the peer-reviewed, revised versions of the most outstanding papers on these topics presented at the ILDAC2015 Conference in Djerba, Tunisia.
Keywords: Water resources development.; Arid regions.; Water security.; Land use.; elektronické knihy; electronic books